2023
DOI: 10.35848/1882-0786/acc568
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz quantum cascade laser considering compositional interdiffusion effect

Abstract: This study presents an experimental demonstration of the crucial role of compositional interdiffusion at interfaces in GaAs/AlGaAs alternating superlattices for developing the terahertz quantum cascade lasers operating at high temperatures. By growing GaAs/Al0.3Ga0.7As superlattices using the molecular beam epitaxy technique, an aluminum interdiffusion width of 0.95 nm (equivalent to ∼3.4 monolayers) is estimated. Incorporating this interdiffusion width as an additional design parameter has resulted in a 20 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A direct comparison with other growth methods reported in the literature is difficult because of differences in crystallographic orientation, interfacial roughness, measurement methodology, probed interfacial area size, and growth conditions. Nevertheless, it is instructive to mention that state-of-the-art VS-grown GaAs/Al x Ga 1– x As(001) thin-film heterostructures (including quantum cascade laser structures) with x in the range of 0.3–0.4 exhibit interfacial widths of 3–4 ML, , which is among the sharpest binary/ternary alloy interfaces quoted in the literature. Impressively, our pulsed VLS growth mode resulted in comparable or even sharper axial interfaces in nanowires, highlighting the importance and the prospects of our findings.…”
Section: Resultsmentioning
confidence: 99%
“…A direct comparison with other growth methods reported in the literature is difficult because of differences in crystallographic orientation, interfacial roughness, measurement methodology, probed interfacial area size, and growth conditions. Nevertheless, it is instructive to mention that state-of-the-art VS-grown GaAs/Al x Ga 1– x As(001) thin-film heterostructures (including quantum cascade laser structures) with x in the range of 0.3–0.4 exhibit interfacial widths of 3–4 ML, , which is among the sharpest binary/ternary alloy interfaces quoted in the literature. Impressively, our pulsed VLS growth mode resulted in comparable or even sharper axial interfaces in nanowires, highlighting the importance and the prospects of our findings.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that neglecting interdiffusion during THz-QCL design can cause obvious discrepancies between the intended and actual wave functions layout. 24) The objective of this study is to provide a quantitative analysis of the impact of interdiffusion scattering on the self-consistent optical gain in THz-QCLs.…”
mentioning
confidence: 99%
“…28) By using APT, it can evaluate several interdiffusion parameters from the buried interfaces, i.e., the parameter of interdiffusion width L, which can be determined by fitting the one-dimensional composition profiles with an error function 29) or a sigmodal function. 30) In our MBE-grown GaAs/Al 0.3 Ga 0.7 As quantum structures, a three monolayers (MLs) interdiffusion width is assumed; 24) parameter of rms, which can be obtained from the reconstruction of the buried interfaces at each z(x, y) surface. Meanwhile, APT can also be used to estimate the out-plane (z axes) correlation length, labeled as Λ ┴ .…”
mentioning
confidence: 99%